A Diagenetic Facies Model for Characterizing Yanan Formation, Ordos Basin, North Central China - Ahmed Mohamed Ahmed Salim, Berihun Mamo Negash, Abubaker Mohamed, . (2017)
Low-resistivity pay is a popular phenomenon in many sedimentary formations, and is present in clastic reservoirs of Yanan formation, Ordos Basin of North Central China. The reservoir quality of the studied sandstones is affected positively and negatively by several diagenetic processes, our classification is based on precipitation of pyrite and feldspar and clay minerals authigenesis.